An alkaline water electrolyzer with nickel electrodes enables efficient high current density operation - Schalenbach, Maximilian; Kasian, Olga; Mayrhofer, Karl (International Journal of Hydrogen Energy, 2018)
Low-temperature industrial water electrolysis is typically conducted using either liquid alkaline electrolytes or acidic polymer electrolyte membranes (PEMs). The latter approach is considered to be more efficient but also more expensive as it requires Pt and Ir based catalysts. This study reports on an alkaline water electrolyzer with Ni electrodes that operates at a current density of 2 A/cm(2) with a cell voltage of 1.85 V, which provides a comparable voltage-current characteristic to the state-of-the-art PEM water electrolyzers. Thin Ni mesh electrodes with surface areas that are thousand times higher than the geometric area were manufactured by an easily scalable and cheap process, i.e. metallurgical hot dip galvanization with subsequent de-alloying. With a thin porous polymer of approximately 140 mu m as the diaphragm a low cell resistance of 0.11 Omega cm(-2) was obtained. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Alkaline water electrolysis; High surface area electrodes; Diaphragm; Cell design; Nickel electrocatalyst